Functional Outcome and Quality of Life After Hypoglossal-Facial Jump Nerve Suture - Volk, Gerd Fabian; Geitner, Maren; Geißler, Katharina; Thielker, Jovanna; Raslan, Ashraf; Mothes, Oliver; Dobel, Christian; Guntinas-Lichius, Orlando (Frontiers in Surgery, 2020)
Background: To evaluate the face-specific quality of life after hypoglossal-facial jump nerve suture for patients with long-term facial paralysis. Methods: A single-center retrospective cohort study was performed. 41 adults (46% women; median age: 55 years) received a hypoglossal-facial jump nerve suture. Sunnybrook and eFACE grading was performed before surgery and at a median time of 42 months after surgery. The Facial Clinimetric Evaluation (FaCE) survey and the Facial Disability Index (FDI) were used to quantify face-specific quality of life after surgery. Results: Hypoglossal-facial jump nerve suture was successful in all cases without tongue dysfunction. After surgery, the median FaCE Total score was 60 and the median FDI Total score was 76.3. Most Sunnybrook and eFACE grading subscores improved significantly after surgery. Younger age was the only consistent independent predictor for better FaCE outcome. Additional upper eyelid weight loading further improved the FaCE Eye comfort subscore. Sunnybrook grading showed a better correlation to FaCE assessment than the eFACE. Neither Sunnybrook nor eFACE grading correlated to the FDI assessment. Conclusion: The hypoglossal-facial jump nerve suture is a good option for nerve transfer to reanimate the facial muscles to improve facial motor function and face-specific quality of life.